Poultry Faeces Management by Bioconversion Technology with Modified GGC 2047 Model - Neupane, S. K.; Sharma, Ram K.; Karki, Shiva Shankar (Journal of Advanced College of Engineering and Management, 2016)
In this report, entitled “Poultry Faeces Management by Bioconversion Technology with Modified GGC 2047 model” focuses on various parameters relating to physico-chemical characteristics of the substrate, fertilizing value of digested poultry waste and potential to create profitability from biogas energy, thus generated and balancing the environmental aspects using poultry waste digestion. Also, biogas may be the tool of energy generation in rural areas while sanitation (waste management) in urban areas of developing countries asNepal. Biogas production from chicken faeces could be obtained more effectively by feeding around 8.5 kg per day. It is concluded that digester could be run by around 2.5 quintal chicken faeces per month. Hence those people, who can manage this quantity of waste, can utilize bio-digester without poultry farm. Journal of Advanced College of Engineering and Management, Vol. 1, 2015, pp. 107-117